Health promotion - The rationale and the obstacles in workplaces with different employment and financial soundness - Krzysztof Puchalski; Elżbieta Korzeniowska (Nofer Institute of Occupational Medicine, 2013)
Background: This paper presents the prevalence of health promotion in workplaces in Poland. It characterises the undertaken actions, their rationale and perceived obstacles. It analyses the diversity of these phenomena in the companies of different financial soundness and level of employment. Material and Methods: The study was conducted with the use of Computer Assisted Telephone Interview in 2010 on the representative national sample of 1002 workplaces hiring more than 50 employees. The data was compared with the results of the survey conducted in 2006, with the use of a Paper and Pencil interview on 611 similar companies. Results: Both studies have shown that 40% of the companies are concerned about their employees' health to a greater extent than they are obliged to by the law. At the same time, more than 80% of the companies have been introducing various modifications and health-oriented actions without definite health intentions. Most companies improve their physical working environment, organise/sponsor medical services, sports activities and try to reduce stress and smoking. Managers have increased their awareness of business benefits received from health promotion. They have displayed more personal involvement in health promotion implementation. The most often mentioned obstacles have included limited financial resources and little interest of employees regarding health issues. Conclusions: The larger and wealthier the company is, the more often health promotion in the company is performed. Such a company is more convinced about an increase in its activities and has more reasons to care about health. Unequal access to health promotion of workers in different companies may contribute to an increase in health inequalities in the working population. Med Pr 2013;64(6):743-754